Principal component analysis in the epidemiology of diarrhoea in calves - Ablaikhan Kadyrov; Altay Ussenbayev; Dariyash Kurenkeyeva; Berdaly Kurenkey; Sarsenbay Abdrakhmanov; Nurlan Tashatov (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The paper is the first to use principal component analysis (PCA) in veterinary epidemiology and aims to identify the most significant agents of diarrhoea in calves. Data were collected from 245 calves on 32 farms within 13 districts of Northern Kazakhstan. Epidemiological data were simulated in R, using standard PCA modules. The data clustering was carried out based on the prevalence of seven enteropathogens for an age group dataset (represented by four animal groups) and a farm type dataset (by three farm types depending on herd size). The simulation revealed that the components identified here for one and two-week calves explained 91.31% of the variance. The first two components of large and middle-sized farms covered 90.3% of the variance. The coordinates corresponding to pathogens were approximately visualised in directions of eigenvectors for each age group and farm type. The coordinate for Cryptosporidium parvum was in directions of eigenvectors for one-to three-week calves and large farms. The coordinate for rotaviruses was in the direction of eigenvectors for four-week calves and medium-sized and small farms. So, PCA can potentially be useful in the clustering of epidemiological datasets and making decisions on control of infectious diseases with a multi-pathogenic nature.